Implementation of Online Learning in Elementary Schools in Makassar City from an Islamic Perspective - Wahyullah Alannasir; Moh Nasir Mahmud; Misykat Malik Ibrahim; St. Syamsudduha (STAI Hubbulwathan Duri, 2022)
This study aims to illustrate the application of online learning, the assessment carried out in terms of student aspects and interactions in online learning in elementary schools. The type of research used is phenomenology with normative and pedagogical theological approaches. The informants were 12 people with details: 4 teachers, 4 parents, and 4 learners. Observation by observing virtual meetings through the TIMS application and WhatssApp chat, while interviews in person and through phone calls. Data analysis is: Colection Data, Condensation Data, Display Data, and Conclusion Drawing/Verifications. The results of this study show that teacher preparation is carried out by compiling lesson plans, documenting material in the form of photos, self-preparation for technology, providing special training to students in operating learning applications, and learning preparation by checking network availability. Implementation of online learning using virtual face-to-face meetings with the Microsoft 365 TEAMS application and conversations through WhatssApp groups. Assessment of the learning process of students in online learning includes aspects of learning implementation, learning motivation, and activeness of students in learning activities. Assessment of learning outcomes with daily assignments and project assignments. The interaction that occurs is predominantly a one-way interaction.